Optic nerve ultrasound in idiopathic intracranial hypertension (Ukrainian Journal of Ophthalmology, 2026)
Backup: Vision loss associated with secondary optic atrophy is the major complication of idiopathic intracranial hypertension (IIH). A potential for the development of severe visual impairment necessitates regular monitoring and determines the importance of ophthalmological examination in patients with this condition. Optic nerve ultrasound (ONUS) enables identification of IIH and monitoring of raised intracranial pressure (ICP) in these patients.Purpose: To investigate the diagnostic potential of ONUS.Materials and Methods: Fifty patients (100 eyes) underwent ONUS using general purpose ultrasound system Sonoline Versa Plus with 8-MHz transducer, before and after treatment for IIH. The control group included 15 healthy volunteers (30 eyes). Depending on the ophthalmoscopic changes, patient eyes were divided into four pre-treatment groups (mild papilledema, 26 eyes; moderate papilledema, 25 eyes; marked papilledema, 21 eyes and optic atrophy secondary to papilledema, 28 eyes) and two post-treatment groups (retinal angiopathy, 65 eyes; and secondary optic atrophy, 35 eyes).Results: The pre-treatment optic nerve diameter in mild, moderate, marked and atrophic papilledema eyes was found to be 5.08 ± 0.18 mm, 5.98 ± 0.45 mm, 6.14 ± 0.37 mm and 5.15 ± 0.72 mm, while that in controls was 4.08 ± 0.25 mm.Conclusion: ONUS is an accurate, fast, non-invasive and economical diagnostic technique for the detection of raised intracranial pressure in IIH.
Keywords: Idiopathic intracranial hypertension; papilledema; optic nerve ultrasound